HISTORICAL EVOLUTION OF ISLAMIC THOUGHT OVER TIME - Barella, Yusawinur; Mahmudin, Mahmudin; Aderus, Andi (Zawiyah: Jurnal Pemikiran Islam, 2023)
This article discusses the history, core teachings, and development of thought within Islam from its pre-Islamic origins to the present day. The Islamic thought presented in this article encompasses various aspects, including historical, social, political, and legal aspects. The researcher adopts a qualitative descriptive method through library research, which involves an in-depth study of various literary sources such as journals, books, and other relevant materials related to the research topic. Additionally, the researcher employs historical methods in this study due to its connection with past events.